Faktor-Faktor yang Mempengaruhi Profitabilitas Bank: Studi pada Perbankan Swasta di Indonesia - Dahyang Ika Leni Wijayani (Politeknik Ganesha Medan, 2023)
This research aim is to investigate the factors that influence bank profitability in Indonesia especially with some banking ratio such as loan to deposit ratio, capital adequacy ratio and non-performing loan. All the independent variables are characteristic measurement for banking sector with profitability as dependent variables. There are 40 private banks in the population who listed on Indonesia Stock Exchange on 2019-2020 and 24 were chosen with purposive sampling. Moreover, multiple linear regression (MLR) with classical assumption test is statistic method to test the hypothesis. The result shows that only loan to deposit ratio which has no influence to return on asset as proxies for profitability. Statistically proven that capital adequacy ratio has a positive impact to profitability, meanwhile non-performing loan has a negative impact to profitability. This research will contribute to the existing theories of liquidity risk and trade off theory between liquidity and profitability.